Lost and Found: The Missing Flamboyant Gothic Door from the Château de Varaignes - Martha Easton (Perspectives Médiévales)
In the late 1920s, the Flamboyant Gothic portal that had graced the Château de Varaignes since the late Middle Ages was sold after the château itself had fallen into disrepair. The townspeople of Varaignes did not know what had become of the door although it was rumored it had been sent to the United States. In 2014, a group of researchers from Varaignes discovered that the door had ended up at Hammond Castle, constructed between 1926 and 1929 in Gloucester, Massachusetts. It was one of the many pieces of architectural salvage from Europe collected by the scientist and inventor John Hays Hammond Jr. and installed in the revivalist medieval-style castle that served as both his home and his laboratory. In following the journey of the Varaignes portal, this paper will discuss the acquisition of architectural elements from Europe by American collectors in the early twentieth century as both a form of philanthropic intervention, but also as cultural imperialism. The Château de Varaignes, now a museum dedicated to the region’s history, particularly textile production, is raising funds to replicate the door in its original location. Just as Hammond used the original Gothic door to evoke the past and lend authenticity to his revivalist castle, the replicated door in Varaignes will serve as a powerful reminder of the lost original.